Not just any toilet – women's solutions to sanitation in informal settlements in Nairobi. Issue 1 (2nd January 2019) - Winter, Samantha; Barchi, Francis; Dzombo, Millicent Ningoma
ABSTRACT: Evidence suggests sanitation development is more effective when women are involved. The purpose of this study was to provide women with an opportunity to share their perspectives and solutions to sanitation in informal settlements. Data were collected through 55 in-depth interviews with women in Mathare Valley informal settlement in Nairobi, Kenya. The most common solution was to build more toilets, but women had a variety of suggestions – including gender-specific solutions. Findings from this study suggest that it is imperative to start addressing women-specific burdens associated with sanitation in informal settlements.